Assessment of Solid Waste from Cruise Ships in the Port of Split - Slišković, Merica; Ukić, Helena; Božić, Katja (Transactions on Maritime Science, 2016)
The aim of this paper is to assess the quantity of solid waste in the port of Split produced by cruisers during the past five years. The increased number of cruising guests in the port ofSplit is associated with more marine litter produced and directly increases a potential impact on the marine environment. To sustainably manage its resources, the city of Split should carefully consider the positive and negative effects of the cruising industry, set up a quality control system in cruising and consider how potential profit impacts on the environment and natural resources.